IMPLEMENTATION OF ERGONOMICS IN THE WORK ENVIRONMENT FOR EMPLOYEE HEALTH AND SAFETY - Gamayudha, Rangga; Mokh Adib Sultan (Dinasti Publisher, 2020)
This reserach based on health issues because of the employee that Appear ergonomical failure. This condition can be a burden for the company peroductivity and performance. Many industries look this issue as a minor issue and they concern not to take this into serious discussions to solve the issue, but this minor issue can effect spesifically Become a major issue for the health and safety of the employees in the company. This research objectives is to describe the implication of ergonomical failure to health and safety of emplyee that can effect the company productivity and performance. By comparing some of Articles that already discuss about this issue, the author want to give insight about how important this issue and give solution from ergonomical view.